Respon Pertumbuhan Beberapa Varietas Kelapa Sawit (Elaeis guineensis Jacq) terhadap Pemberian Trichokompos Bahan Baku Kelapa Sawit di Pembibitan Utama - Sepriadi Berutu; Islan Islan; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The development of oil palm plantation is closely related to the availability of seed quality. Seed quality will determine whether or not the growth and production of the commodity. Trichocompost applications made from palm fronds provide a good response to the growth of palm oil. Research aims to determine the growth response of some varieties of seedlings of oil palm (Elaeis guineensis Jacq) on the application of Trichocompost palm oil raw materials in main nursery and which Trichocompost is the best against the growth response of some varieties of oil palm seedlings and interaction of several varieties of seedlings of oil palm (Elaeis guineensis Jacq) against Trichocompost application raw materials palm oil in the main nursery. Research was conducted using a completely randomized design (CRD) 2 factors: oil palm varieties (PPKS, Topaz and Socfindo) and Trichocompost (palm fronds, palm leaf and whole palm fronds) with three replications. The experiment was conducted in March-July 2016 at the Experimental Farm, Faculty of Agriculture, University of Riau. The results showed that significant effect on native varieties on height increase, the number of leaves increase, diameter hump increase, the ratio of the canopy and root, and dry weight of oil palm seedlings. Tenera variety of oil palm seedlings DXP Marihat PPKS origin is the best growth response compared to other varieties. Keywords: Palm oil, varieties and Trichocompost